Professional learning as a predictor for instructional quality: a secondary analysis of TALIS - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2018)
The purpose of this study is to examine the effect of teachers' professional learning opportunities on instructional quality, which represents a combined approach of behaviorist, cognitivist, and constructivist principles in teaching. We incorporated professional learning communities (PLCs), professional development (PD) days, as well as 3 PD types (traditional, reform-based, and informal) to provide a comprehensive account of teachers' professional learning opportunities. Using the extant large-scale data, the Teaching and Learning International Survey (TALIS), from 3,213 middle-school teachers in Turkey, we found that PLCs and reform-based PD activities produced statistically significant effects on instructional quality, ranging from high to moderate effects, all other PD variables held constant. Discussion on the results was centered on the schools for being a venue for professional learning and the potential of collaborative structures to promote teachers' development.
Keywords: Instructional quality; professional learning; professional learning communities; professional development; TALIS; LOCAL SYSTEMIC CHANGE; SCALE RELIABILITY; TEACHER; CLASSROOM; IMPACT; ANTECEDENTS; COMMUNITY; KNOWLEDGE; DESIGN; SAMPLE